Coarse spray and drinking water vaccination against infectious bursal disease in commercial broilers - Castellanos C., Diana (2012)
Vaccination against the Infectious Bursal disease via spray and via drinking water was compared in broilers using a vaccine with intermediate strains in a vaccination programme at 7 and 17 days of age. A total of 69 100 Cobb Vantress 500 chicks in a commercial farm were divided in two similar groups. Group A was vaccinated via spray and group B was vaccinated via drinking water. Then, 50 chicks at 29 days of age from each group were relocated to an experimental farm and challenged with a standard F52/70 strain. Bursal index, macroscopic and microscopic lesions, and serological response were monitored in both challenged and non-challenged birds. Minor clinical signs of short duration, including depressions and diarrhea were observed during three days in challenged birds in both experimental groups showing the level of protection conferred by the vaccine in both groups; however, greater number of birds vaccinated via drinking water showed depression (p<0.05). No statistical differences between challenged and non-challenged groups were found in bursal index, histological bursal lesions, and serology. The bursal indexes and degree of microscopic lesions indicated bursal atrophy for both vaccination routes, showing similar activity and degree of replication of the vaccine virus. It is concluded that vaccination via spray and via drinking water can be used as methods of vaccination against Infectious Bursal disease.